PERAN SISTEM INFORMASI MANAJEMEN DALAM MENDUKUNG PROSES PENGAMBILAN KEPUTUSAN ORGANISASI SECARA EFEKTIF DAN STRATEGIS - Siti Sahfina; Muhammad Irwan Padli Nasution (INTERNATIONAL, Journal of Sharia Business Management, 2025)
This study discusses the role of Management Information Systems (MIS) in supporting organizational decision-making processes in the digital era. Using a descriptive qualitative approach and literature review method, the research examines various theories, functions, and applications of MIS across different sectors. The findings indicate that MIS plays a crucial role in providing accurate, relevant, and timely information for managers to formulate, implement, and evaluate both strategic and operational decisions. Furthermore, MIS enhances the effectiveness of Decision Support Systems (DSS) by reducing uncertainty and improving decision quality. The study emphasizes that the successful implementation of MIS depends Not only on the technology used but also on the readiness of human resources and the supporting organizational structure. Therefore, an effective MIS implementation can be a key factor in improving organizational performance and competitiveness.